School Readiness: Readiness Children Seen from The Whole Aspect of Early Childhood Development - Seran, Theodorina Novyani; Haryono, Haryono; Anni, Catharina Tri (Journal of Primary Education, 2017)
This research aims to describe and analyze Ã¢â‚¬Å“The Readiness of Children in the age 5-6 Years of Entering Primary SchoolÃ¢â‚¬Â from some aspects which includes (1) readiness of morality aspects and religious values, (2) readiness of physical aspects of motor, (3) readiness of cognitive aspects, (4) readiness of language aspects, (5) readiness of social-emotional in PAUD Cerdas Based on the Natural Environment. The type of this research is qualitative research. The data were collected using observation, interview, and documentation study. Data credibility is checking by source triangulation techniques and methods. The analysis was done by using type of interactive in data analysis according to Miles and Huberman. The result of this research shows that the readiness of morality aspects and religious values, the readiness of physical aspects of motor, the readiness of cognitive aspects, the readiness of language aspects, and the readiness of social Ã¢â‚¬â€œ emotional in PAUD Cerdas has been ready as expected so it makes possible to the children to continue the education in elementary school and implict in annual plan activities which has been programmed into the school curriculum. According to the research, the advice for the parrents is recognize the standard of achievement of all aspects of the children in the age 5-6 years, so it is same with all that used by teacher at school. The advice for school is design a special curriculum which related with the base of the school that has been running.